Risk Factors for Neonatal Sepsis in Pregnant Women with Premature Rupture of the Membrane. (1st October 2018) - Ocviyanti, Dwiana; Wahono, William Timotius
Abstract : Background. Premature rupture of the membrane (PROM) is associated with high maternal as well as perinatal morbidity and mortality risks. It occurs in 5 to 10% of all pregnancy while incidence of amniotic membrane infection varies from 6 to 10%. This study aimed to determine the incidence of neonatal sepsis in Cipto Mangunkusumo Hospital and the risk factors. Methods. A cross-sectional study was done in Cipto Mangunkusumo Hospital, Jakarta, from December 2016 to June 2017. The study used total sampling method including all pregnant women with gestational age of 20 weeks or more experiencing PROM, who came to the hospital at that time. Samples with existing comorbidities such as diabetes mellitus or other serious systemic illnesses such as heart disease or autoimmune condition were excluded from the analysis. Results. A total of 405 pregnant women with PROM were included in this study. There were 21 cases (5.2%) of neonatal sepsis. The analysis showed that risk of neonatal sepsis was higher in pregnant women with prolonged rupture of membrane for ≥ 18 hours before hospital admission (OR 3.08), prolonged rupture of membrane for ≥ 15 hours during hospitalization (OR 7.32), and prolonged rupture of membrane for ≥ 48 hours until birth (OR 5.77). The risk of neonatal sepsis was higher in preterm pregnancy with gestational age of <37 weeks (OR 18.59). Conclusion. Risk of neonatal sepsis is higher in longer duration of prolonged rupture of membrane as well as preterm pregnancy.